Variations in the complement regulatory genes factor H (CFH) and factor H related 5 (CFHR5) are associated with membranoproliferative glomerulonephritis type II (dense deposit disease) - Abrera-Abeleda, M A; Nishimura, C; Smith, J L H; Sethi, S; McRae, J L; Murphy, B F; Silvestri, G; Skerka, C; Józsi, M; Zipfel, P F; Hageman, G S; Smith, R J H (Journal of medical genetics, 2006)
Introduction: Membranoproliferative glomerulonephritis type II or dense deposit disease (MPGN II/DDD) causes chronic renal dysfunction that progresses to end stage renal disease in about half of patients within 10 years of diagnosis. Deficiency of and mutations in the complement factor H (CFH) gene are associated with the development of MPGN II/DDD, suggesting that dysregulation of the alternative pathway of the complement cascade is important in disease pathophysiology. Subjects: Patients with MPGN II/DDD were studied to determine whether specific allele variants of CFH and CFHR5 segregate preferentially with the MPGN II/DDD disease phenotype. The control group was compromised of 131 people in whom age related macular degeneration had been excluded. Results: Allele frequencies of four single nucleotide polymorphisms in CFH and three in CFHR5 were significantly different between MPGN II/DDD patients and controls. Conclusion: We have identified specific allele variants of CFH and CFHR5 associated with the MPGN II/DDD disease phenotype. While our data can be interpreted to further implicate complement in the pathogenesis of MPGN II/DDD, these associations could also be unrelated to disease pathophysiology. Functional studies are required to resolve this question.